Black Power beyond Borders
IX, 214 p.
Keywords: This groundbreaking volume examines the transnational dimensions of Black Power - how Black Power thinkers and activists drew on foreign movements and vice versa how individuals and groups in other parts of the world interpreted 'Black Power,' from African liberation movements to anti-caste agitation in India to indigenous protests in New Zealand.